Peran Budaya Kampus dalam Pembentukan Karakter Kebersamaan Taruna Pelayaran - Krisa, Dival Jeri (Jurnal Cakrawala Bahari, 2025)
This study examines the contribution of campus traditions and cultural practices in fostering camaraderie among cadets at the Politeknik Pelayaran Sumatera Barat. Conducted 2025, the research adopts a mixed-methods design that combines quantitative survey data with qualitative insights from in-depth interviews. Core traditions—such as weekly flag ceremonies, orientation programs, and maritime symbols—emerge as key instruments for instilling collective values and reinforcing social unity. A survey of 50 cadets indicates consistently high levels of camaraderie and collectivism. These findings are complemented by interviews with 20 informants, which highlight the role of institutional culture in developing emotional resilience, a strong sense of belonging, and teamwork skills essential for navigating the pressures of the maritime profession The results reaffirm Durkheim’s theory that rituals function as instruments of social cohesion, while also contextualizing its relevance within maritime education in Indonesia. Theoretically, this research enriches sociological discourse by situating maritime traditions within broader frameworks of collective identity formation. Practically, it offers a strategic model for character development, positioning traditions as intentional mechanisms to cultivate both professional expertise and interpersonal solidarity. Policy recommendations emphasize the need for maritime academies to sustain, adapt, and institutionalize traditions as a strategy for preparing competent and resilient cadets. Overall, this study bridges theoretical perspectives with practical applications, providing valuable insights for educators, policymakers, and maritime institutions seeking to enhance holistic cadet development through culturally embedded practices. keyword: traditions, campus culture, collective character, maritime cadets, qualitative research